Tone compensation of amplitude modulation matrix via minimal Munsell value error based laser printer model. (11th June 2015) - Su, H.; Yi, Y.; Liu, J.; Yuan, Y.
Abstract : A laser printer model is required to help suppress non-linear distortions associated with laser printer outputs. A minimal Munsell value error based printer model is proposed and applied to compensate for the tone of the amplitude modulation (AM) matrix. A conversion method for printouts is established with Munsell values as intermediate values. Then, through recurrent parameter modifications and simulations, the optimal parameters of the stochastic dot model of the printer are obtained by calculating the minimum Munsell value error. Finally, the dither matrix is converted to a binary pattern with a given grey level, and the AM matrix thresholds are modified to make the simulated grey level of the binary pattern close to the given grey level. An experimental assessment of the proposed method, in which the difference between the corresponding Munsell values of printouts and ideal values is analysed, indicates that the method can significantly restrain the influence of non-linear characteristics of printers.